ANTERIOR CROSSBITE TREATMENT USING TONGUE BLADE IN EIGHT-YEARS-OLD CHILDREN VIA TELEDENTISTRY DURING PANDEMIC (PERAWATAN GIGITAN SILANG ANTERIOR MENGGUNAKAN TONGUE BLADE PADA ANAK USIA 8 TAHUN VIA TELEDENTISTRY DI MASA PANDEMI) - Hillda Herawati; Lisna Wati Solihat (Fakultas Kedokteran Gigi Unjani, 2022)
Anterior crossbite is a condition in which one or more of the upper front teeth are located lingually to the lower front teeth during centric occlusion. Dentistry involves close face-to-face interactions with patients, so during the COVID-19 pandemic, it has been largely suspended. Teledentistry is a solution to continue the practice of dentistry during this pandemic. This case report describes an eight-year-old insecure boy who came with a complaint that his upper left front tooth had grown behind his lower front teeth since four months ago. The patient was diagnosed with Class 1 Angle malocclusion types 1 and 3. The patient education and instructions treatment used a tongue blade via teledentistry via video call. The consideration of using this treatment is due to a not ideal condition caused by the COVID-19 pandemic. This technique was done one or two hours a day. The result was twenty-one tooth malocclusion was corrected. The result indicates by the twenty-one tooth position which has passed the mandibular incisor to the labial direction. The conclusion suggests that early treatment, in this case, is necessary to modify the growth direction to prevent further malocclusion. It is also concluded that Anterior crossbite treatment via teledentistry using a tongue blade gives significant results. DOI : 10.54052/jhds.v1n3.267-274